Evaluasi Biaya Perawatan Intensif Pasien COVID-19 Di RSUP Persahabatan Jakarta: Pendekatan Activity Based Costing - Putra, Andika Chandra (Majalah Kedokteran Andalas, 2024)
Facing the COVID-19 pandemic, the healthcare system, especially in Indonesia, encountered significant operational and financial challenges, particularly concerning intensive care costs. RSUP Persahabatan, serving as a national referral center, consistently managed COVID-19 patients ranging from moderate to critical degrees. Recognizing the importance of cost evaluation for efficiency enhancement, this study aimed to meticulously examine the unit cost of intensive care for COVID-19 patients using the Activity Based Costing (ABC) approach. In-depth analysis revealed that the intensive care unit at RSUP Persahabatan comprises 14 supporting activities and offers 61 service products. Both direct and indirect costs for each activity were successfully identified and quantified. Further, when juxtaposed with the INA-CBGs rates set by the 2023 Indonesian Health Minister's Regulation, it became evident that RSUP Persahabatan's ICU achieved remarkable cost efficiency. These findings not only provide invaluable insights for RSUP Persahabatan but also offer strategic recommendations for other healthcare institutions in the evaluation and optimization of COVID-19 intensive care costs.